Surface protection film, optical component including the same, and display device including the same

By using the surface protective film composed of hard coating, basic layers and bonding layers on the foldable display device, the problem of flexible and impact resistance in existing technologies is solved, and excellent folding at low temperature and high temperature Reliability and excellent appearance.

CN114763453BActive Publication Date: 2025-01-24SAMSUNG SDI CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210033079.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-01-12
Filing Date
2022-01-12
Publication Date
2025-01-24
Estimated Expiration
2042-01-12

AI Technical Summary

Technical Problem

Existing surface protective films cannot achieve flexibility and impact resistance on foldable display devices, and the thermoplastic polyurethane films have poor appearance due to gel formation and striped patterns.

Method used

A surface protective film composed of a hard coating, a base layer and an adhesive layer is used. The base layer is formed by a solution casting method, and the hard coating is composed of a urethane (meth)acrylate hard coating composition. The adhesive layer is formed from a hydroxyl-containing (meth)acrylic adhesive composition or a silicone adhesive composition.

Benefits of technology

The excellent folding reliability at low temperature and high temperature improves impact resistance, abrasion resistance and non -slip, while maintaining an excellent appearance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003467205870000261
    Figure BDA0003467205870000261
Patent Text Reader

Abstract

The present invention relates to a surface protection film, an optical component including the same, and a display device including the same. The surface protection film comprises: a hard coating layer, a base layer, and an adhesive layer stacked in sequence in a specified order, wherein a laminate of the hard coating layer and the base layer may have a storage modulus of about 900 MPa to about 1500 MPa at ‑20° C. and a storage modulus of about 15 MPa to about 100 MPa at 85° C.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Citations of Related Applications

[0002] This application claims the benefit of Korean Patent Application No. 10-2021-0004292 filed on January 12, 2021, in the Korean Intellectual Property Office, the disclosure of which is incorporated herein in its entirety by reference. Technical Field

[0003] The present invention relates to a surface protection film, an optical component including the same, and a display device including the same. Background Art

[0004] At present, the development of foldable display devices has been achieved. Therefore, surface protection films have been developed to protect foldable display devices, especially window films, against the external environment. Although typical surface protection films that give priority to protection against the external environment and rework characteristics have been produced, typical surface protection films cannot achieve flexibility and therefore cannot be applied to foldable display devices.

[0005] The surface protection film is arranged on the outermost surface of the display device. Therefore, the surface protection film is required to have not only flexibility but also impact resistance. The surface protection film includes a base layer and a hard coating layer stacked on one surface of the base layer. However, since the base layer does not usually show adhesive properties, the surface protection film is attached to the optical element by an adhesive layer. The film composed of the base layer and the hard coating layer does not experience the problem of impact resistance, but the film composed of the adhesive layer, the base layer and the hard coating layer can show different impact resistance depending on the adhesive layer.

[0006] A thermoplastic polyurethane (TPU) film may be used as a base layer. However, the thermoplastic polyurethane film provides a poor appearance due to gel formation and a noticeable stripe pattern, resulting in a restriction on use on the outermost surface of a display device. Specifically, since the screen size of the display device is maximized and a high screen resolution is required, the poor appearance can be easily recognized.

[0007] The background technology of the present invention is disclosed in Japanese Unexamined Patent Publication No. 2016-060117 and the like. Summary of the invention

[0008] One aspect of the present invention is to provide a surface protection film having excellent properties in terms of impact resistance and folding reliability at low and high temperatures.

[0009] Another aspect of the present invention is to provide a surface protection film having improved properties in terms of abrasion resistance, scratch resistance and anti-slip properties.

[0010] Another aspect of the present invention is to provide a surface protection film having an excellent appearance.

[0011] One aspect of the present invention relates to a surface protection film.

[0012] Aspect 1. A surface protection film comprises a hard coating layer, a base layer and an adhesive layer stacked in sequence in a stated order, wherein a laminate of the hard coating layer and the base layer can have a storage modulus of about 900 MPa to about 1500 MPa at -20°C and a storage modulus of about 15 MPa to about 100 MPa at 85°C.

[0013] Aspect 2. A surface protection film includes a hard coating layer, a base layer, and an adhesive layer sequentially stacked in a specified order, wherein the base layer includes a polyurethane film formed by a solution casting method and has a Young's modulus of about 80 MPa to about 500 MPa at 25°C.

[0014] Aspect 3. In aspect 2, the laminate of the hard coating layer and the base layer may have a storage modulus of about 900 MPa to about 1500 MPa at -20°C and a storage modulus of about 15 MPa to about 100 MPa at 85°C.

[0015] Aspect 4. In aspect 1, the base layer may include a cast polyurethane film, a polyimide film, or a polyethylene terephthalate film.

[0016] Aspect 5. In any one of aspects 1 to 4, the base layer may have a thickness of about 75 μm to about 200 μm.

[0017] Aspect 6. In any one of aspects 1 to 5, the base layer may have a fracture elongation of about 200% or more at 25°C.

[0018] Aspect 7. In any one of aspects 1 to 6, the base layer may have a storage modulus of about 900 MPa to about 1500 MPa at -20°C and a storage modulus of about 15 MPa to about 100 MPa at 85°C.

[0019] Aspect 8. In any one of aspects 1 to 7, the base layer may have a haze of about 1% or less.

[0020] Aspect 9. In any one of aspects 1 to 8, the adhesive layer may have a storage modulus of about 10 kPa to about 500 kPa at -20°C and a storage modulus of about 10 kPa to about 500 kPa at 60°C.

[0021] Aspect 10. In any one of Aspects 1 to 9, the adhesive layer may include a (meth)acrylic ((meth)acrylic) adhesive layer formed by an adhesive composition, wherein the adhesive composition comprises: a monomer mixture of a hydroxyl-containing (meth)acrylic copolymer, particles or a particle mixture comprising at least one selected from organic particles and inorganic particles, and an initiator; or a silicone-based adhesive layer formed by an adhesive composition comprising an alkenyl-containing organopolysiloxane.

[0022] Aspect 11. In aspect 10, the organic particles may include core-shell type organic nanoparticles.

[0023] Aspect 12. In any one of aspects 10 and 11, the core-shell type organic nanoparticles may satisfy the relationship (1):

[0024] Tg(c) <Tg(s),---(1)

[0025] Wherein Tg(c) is the glass transition temperature of the core (unit: °C), and Tg(s) is the glass transition temperature of the shell (unit: °C).

[0026] Aspect 13. In aspect 10, the inorganic particles may include at least one selected from the group consisting of metal oxides, metal titanates, sulfides, selenides, and tellurides.

[0027] Aspect 14. In any of aspects 10 to 13, the monomer mixture may include from about 5 weight percent (wt%) to about 40 wt% of the hydroxyl-containing (meth)acrylate and from about 60 wt% to about 95 wt% of the comonomer.

[0028] Aspect 15. In aspect 10, the alkenyl-containing organopolysiloxane may include at least one selected from component (i) and component (ii):

[0029] Component (i): Each molecule has at least one Si-coupled C3 to C 10 alkenyl organopolysiloxane; and

[0030] Component (ii): an organopolysiloxane having at least one Si-coupled vinyl group per molecule.

[0031] Aspect 16. In any one of Aspects 1 to 15, the hard coating layer can be formed by a urethane (meth) acrylate hard coating composition, the composition comprising: a first urethane (meth) acrylate oligomer, a second urethane (meth) acrylate oligomer, a (meth) acrylate monomer, aluminum oxide, an initiator, and at least one selected from a fluorine-based additive and a silicone additive.

[0032] Aspect 17. In any one of aspects 1 to 16, the hard coating layer may have a water contact angle of about 100° or more at 25°C.

[0033] Another aspect of the present invention relates to an optical component.

[0034] Aspect 18. An optical member includes the surface protection film according to the present invention.

[0035] Aspect 19. In aspect 18, the optical member may include a window film and a surface protection film formed on one surface of the window film.

[0036] Other aspects of the present invention relate to a display device including the surface protection film according to the present invention. DETAILED DESCRIPTION

[0037] Hereinafter, embodiments of the present invention will be described in detail.

[0038] Herein, "(meth)acryloyl" refers to acryloyl and / or methacryloyl.

[0039] Herein, the "storage modulus" of the adhesive layer is measured under the self-strain condition of 1% strain while increasing the shear rate from 0.1 rad / s to 100 rad / s using a dynamic viscoelasticity instrument (ARES G2, TAInstrument). The storage modulus is measured while increasing the temperature from -20°C to 90°C at a heating rate of 5°C / min. In the measurement of the storage modulus, the specimen is prepared by stacking a 500 μm thick adhesive layer and then punching the laminate using a puncher with a diameter of 8 mm.

[0040] Herein, the “Young's modulus” of the base layer was evaluated on a V-type test specimen according to ASTM D638, specifically through a tensile test experiment conducted at 25° C. and at a rate of 100 mm / min using a UTM system (Intron Technology Co., Ltd.).

[0041] Herein, the "storage modulus" of the base layer is measured relative to the base layer using a dynamic mechanical analyzer (DMA), specifically in a tensile test mode at a frequency of 1 Hz while increasing the temperature from -70°C to 120°C at a heating rate of 2°C / min, and represents the storage modulus at -20°C and the storage modulus at 85°C.

[0042] Herein, the "storage modulus" of the laminate of the hard coating and the base layer is measured relative to the laminate using a dynamic mechanical analyzer (DMA), specifically in a tensile test mode at a frequency of 1 Hz while increasing the temperature from -70°C to 120°C at a heating rate of 2°C / min, and represents the storage modulus at -20°C and the storage modulus at 85°C.

[0043] Herein, the average particle size of organic particles refers to the particle size of organic particles as measured using Zetasizer nano-ZS (Malvern Inc.) in a water-based solvent (aqueous solvent) or an organic solvent and expressed in Z-mean units, and the particle size thereof is confirmed by SEM / TEM observation.

[0044] Herein, the average particle size of the inorganic particles refers to D50, as measured using a particle analyzer. D50 may be measured using a particle analyzer after dispersing the inorganic particles in a solvent at 25° C. for 3 min, or may be obtained by referring to a commercially available product catalog.

[0045] As used herein, to express a specific numerical range, the expression “X to Y” means “X≤and≤Y”.

[0046] The surface protection film according to the present invention has excellent folding reliability at both low and high temperatures and achieves significant improvements in impact resistance, wear resistance and scratch resistance. Therefore, the surface protection film according to the present invention can be arranged on the outermost surface of a display device to protect a variety of optical elements, such as window films, etc., arranged inside a display device to prevent external impacts, and can be applied to a foldable display device. In one embodiment, the surface protection film can be used as a surface protection film to protect a window film.

[0047] The surface protection film according to the present invention achieves significant improvements in impact resistance and has excellent folding reliability at low and high temperatures. Therefore, the surface protection film according to the present invention has an impact resistance evaluation result of 18 cm or more, for example, 18 cm to 30 cm, as measured by the method described in the experimental examples, and does not undergo lifting, peeling and / or bubble generation even after 100,000 or more folding and unfolding cycles in the folding reliability evaluation at -20°C and 60°C, as measured by the method described in the experimental examples.

[0048] Specifically, even with the adhesive layer described below, the surface protection film according to the present invention achieves significant improvement in impact resistance. As described below, the surface protection film includes a hard coating, a base layer and an adhesive layer stacked in a specified order, and the impact resistance of the surface protection film is measured on the hard coating side. Generally, since the adhesive layer is softer than the hard coating and the base layer, the impact resistance can even be partially achieved by the adhesive layer. The adhesive layer is an essential layer for the surface protection film to be connected to the optical element, and therefore the adhesive layer is considered in the impact resistance evaluation.

[0049] The surface protection film according to the present invention has an excellent appearance. In this article, "excellent appearance" means that when the surface protection film is irradiated with light on the hard coating side, the entire surface protection film does not show any stripe pattern, gel and / or opacity. Stripe pattern, gel and / or opacity can be produced by a base layer, a hard coating or an adhesive layer alone or by a combination of a base layer, a hard coating and an adhesive layer. The appearance of the surface protection film can be achieved by all of the base layer, the hard coating and the adhesive layer. The surface protection film according to the present invention provides an excellent appearance by controlling all of the base layer, the hard coating and the adhesive layer.

[0050] The surface protection film according to one embodiment of the present invention comprises a hard coating, a base layer and an adhesive layer stacked in a specified order. In one embodiment, the surface protection film has a three-layer structure, wherein the hard coating is directly formed on the base layer and the adhesive layer is directly formed on the base layer. In this article, "directly formed" means that no other adhesive layer or bonding layer is inserted between the base layer and the hard coating and between the base layer and the adhesive layer.

[0051] In the surface protection film, the laminate of the base layer and the hard coating layer has a storage modulus of about 900 MPa to about 1500 MPa at -20°C and a storage modulus of about 15 MPa to about 100 MPa at 85°C. Therefore, compared with a typical surface protection film, the surface protection film achieves significant improvements in impact resistance and folding reliability at both high and low temperatures. When the storage modulus of the laminate of the base layer and the hard coating layer at -20°C and 85°C is within the above specific range, the surface protection film can have the effect of the present invention.

[0052] The storage modulus of the laminate of the base layer and the hard coating layer at -20°C and 85°C can be achieved by forming the hard coating layer using the hard coating composition described below while controlling the Young's modulus of the base layer. More preferably, the above storage modulus is achieved by additionally controlling the thickness of the base layer and the hard coating layer.

[0053] Preferably, the base layer is formed using a cast polyurethane film. Compared with a surface protection film including a typical polyurethane film, the surface protection film according to the present invention can achieve significant improvements in impact resistance and folding reliability.

[0054] For example, the laminate of the base layer and the hard coat layer can have a storage modulus of 900 MPa, 950 MPa, 1,000 MPa, 1,050 MPa, 1,100 MPa, 1,150 MPa, 1,200 MPa, 1,250 MPa, 1,300 MPa, 1,350 MPa, 1,400 MPa, 1,450 MPa, or 1,500 MPa, as measured at -20°C, and a storage modulus of 15 MPa, 20 MPa, 25 MPa, 30 MPa, 35 MPa, 40 MPa, 45 MPa, 50 MPa, 55 MPa, 60 MPa, 65 MPa, 70 MPa, 75 MPa, 80 MPa, 85 MPa, 90 MPa, 95 MPa, or 100 MPa, as measured at 85°C.

[0055] Preferably, the laminate of the base layer and the hard coating layer has a storage modulus of 900 to 1,200 MPa, more preferably 1,100 to 1,500 MPa at -20° C. Within this range, the effects of the present invention can be ensured while enabling easy production of the laminate of the base layer and the hard coating layer.

[0056] Preferably, the laminate of the base layer and the hard coating layer has a storage modulus of 50 to 90 MPa, more preferably 60 to 80 MPa at 85° C. Within this range, the effects of the present invention can be ensured while enabling easy production of the laminate of the base layer and the hard coating layer.

[0057] Base Layer

[0058] The base layer is inserted between the hard coating layer and the adhesive layer to support the hard coating layer and the adhesive layer while improving impact resistance and folding reliability at low and high temperatures. The base layer can help improve the impact resistance and folding reliability of the surface protection film including the adhesive layer described below.

[0059] The base layer may have a Young's modulus of about 80 MPa to about 500 MPa at 25° C. Within this range, the base layer may help improve impact resistance and flexibility at low and high temperatures.

[0060] For example, the base layer may have a Young's modulus of 80 MPa, 85 MPa, 90 MPa, 95 MPa, 100 MPa, 105 MPa, 110 MPa, 115 MPa, 120 MPa, 125 MPa, 130 MPa, 135 MPa, 140 MPa, 145 MPa, 150 MPa, 155 MPa, 160 MPa, 165 MPa, 170 MPa, 175 MPa, 180 MPa, 185 MPa, 190 MPa, 195 MPa, 200 MPa, 300 MPa, 400 MPa or 500 MPa, as measured at 25° C. Preferably, the base layer has a Young's modulus of 80 MPa to 300 MPa, more preferably 100 MPa to 200 MPa at 25° C.

[0061] The base layer may have a storage modulus of about 900 MPa to about 1500 MPa, specifically 900 MPa to 1200 MPa at -20°C. Within this range, the base layer can assist the film production process while ensuring excellent folding reliability at low temperatures. For example, the base layer may have a storage modulus of 900 MPa, 950 MPa, 1,000 MPa, 1,050 MPa, 1,100 MPa, 1,150 MPa, 1,200 MPa, 1,250 MPa, 1,300 MPa, 1,350 MPa, 1,400 MPa, 1,450 MPa, or 1,500 MPa, as measured at -20°C.

[0062] The base layer may have a storage modulus of about 15 MPa to about 100 MPa, specifically 50 MPa to 90 MPa at 85 ° C. Within this range, the base layer can assist the film production process while ensuring excellent folding reliability under high temperature / high humidity conditions. For example, the base layer may have a storage modulus of 15 MPa, 20 MPa, 25 MPa, 30 MPa, 35 MPa, 40 MPa, 45 MPa, 50 MPa, 55 MPa, 60 MPa, 65 MPa, 70 MPa, 75 MPa, 80 MPa, 85 MPa, 90 MPa, 95 MPa or 100 MPa, as measured at 85 ° C.

[0063] In one embodiment, the base layer may be formed by a cast polyurethane (CPU) film formed by a solution casting method. When the base layer is formed by a cast polyurethane (CPU) film produced by a solution casting method and has the above-mentioned Young's modulus at 25°C, significant improvements in impact resistance and flexibility at low and high temperatures can be achieved. For a base layer that does not have a Young's modulus of 80MPa to 500MPa at 25°C or includes a polyurethane film formed by a specific method, such as melt extrusion, etc., rather than a solution casting method, the surface protection film has much lower impact resistance and folding reliability than the surface protection film according to the present invention and shows a poor appearance.

[0064] The solution casting method is a method of producing a polyurethane film by applying a solution containing a polyurethane resin (polyol, isocyanate curing agent, additives, etc.) and a solvent to a non-sticky surface, and then volatilizing the solvent at a high temperature and thermally curing. The inventors of the present invention have confirmed that the polyurethane film produced by the solution casting method has a high modulus compared to the thermoplastic polyurethane (TPU) film produced by a typical melt extrusion method, even with the same thickness, thereby achieving a significant improvement in impact resistance while providing an excellent appearance. When irradiated with light, the cast polyurethane (CPU) film produced by the solution casting method does not show any streak pattern, gel and / or opacity compared to the thermoplastic polyurethane (TPU) film produced by a typical melt extrusion method, and thus can assist in improving the appearance of the surface protection film.

[0065] Polyurethane resin can be prepared from di- or higher multifunctional polyols and di- or higher multifunctional isocyanates. Polyols can include at least one selected from aromatic polyols, aliphatic polyols and alicyclic polyols. Preferably, polyols are polyurethanes formed from aliphatic polyols and / or alicyclic polyols. Polyols can include at least one selected from the following: polyester diols, polycarbonate diols, polyolefin diols, polyether diols, polythioether diols, polysiloxane diols, polyacetal diols and polyesteramide diols, but are not limited thereto. Multifunctional isocyanates can include any aliphatic, alicyclic or aromatic isocyanates. Chain extenders can include diols, for example, aliphatic diols, amino alcohols, diamines, hydrazines, hydrazides or mixtures thereof. In the preparation of thermoplastic polyurethanes, catalysts for promoting the formation of carbamate bonds can further include tin compounds, for example, tin salts of carboxylic acids, amines, for example, dimethylcyclohexylamine or triethylenediamine, etc. Other typical components may also be included in the preparation of thermoplastic polyurethanes, such as surfactants, flame retardants, fillers, pigments, and the like.

[0066] In another embodiment, the base layer may include a polyimide film and / or a polyethylene terephthalate film.

[0067] The base layer having a Young's modulus of about 80 MPa to about 500 MPa at 25° C. can be obtained by adjusting the molecular weight of the raw materials of the base layer, such as polyol, polyimide, polyethylene terephthalate, etc., during the formation of the base layer. The method of adjusting the molecular weight of the raw materials of the base layer, such as polyol, etc., is well known to those skilled in the art.

[0068] The base layer may have an elongation at break of about 200% or more, for example, 200%, 250%, 300%, 350%, 400%, 450%, 500%, 550%, 600%, 650%, 700%, 750%, 800%, preferably 200% to 800%, more preferably 400% to 800%, as measured at 25° C. Within this range, folding reliability can be ensured.

[0069] The base layer may have a haze of about 1% or less, specifically 0.5% or less, as measured using a haze meter at a wavelength of 380 nm to 780 nm according to ASTM D 1003-95 5 ("Standard Test for Haze and Luminous Transmittance of Transparent Plastic"). Within this range, the base layer can provide a surface protective film capable of ensuring excellent appearance without gel formation, etc.

[0070] The base layer may have a thickness of about 75 μm to about 200 μm, specifically 100 μm to 150 μm. Within this range, the base layer may provide a thin surface protection film capable of improving impact resistance and folding reliability.

[0071] Hard coating

[0072] The hard coating layer is formed on one surface of the base layer and can help the surface protection film achieve significant improvements in impact resistance and flexibility. The hard coating layer can help the laminate of the base layer and the hard coating layer achieve the above-mentioned modulus.

[0073] The hard coating layer may be formed of a urethane (meth)acrylate-based hard coating composition including a first urethane (meth)acrylate oligomer, a second urethane (meth)acrylate oligomer, a (meth)acrylate monomer, aluminum oxide, and an initiator.

[0074] The first urethane (meth)acrylate oligomer has a lower elongation than the second urethane (meth)acrylate oligomer. According to the present invention, the hard coating composition includes two types of urethane (meth)acrylate oligomers having different elongations to help improve impact resistance and folding reliability.

[0075] Preferably, the first urethane (meth) acrylate oligomer has a greater number of functional groups and a lower elongation than the second urethane (meth) acrylate oligomer, although its weight average molecular weight is smaller than that of the second urethane (meth) acrylate oligomer. According to the present invention, the hard coating composition includes two types of urethane (meth) acrylate oligomers with different elongations to help improve the impact resistance and folding reliability of the surface protection film.

[0076] The first carbamate (meth) acrylate oligomer is a seven to ten functional (meth) acrylate oligomer and may have a weight average molecular weight of about 1,000 g / mol to less than about 4,000 g / mol and an elongation of about 1% to less than about 15%. Within this range, the first carbamate (meth) acrylate oligomer helps improve the impact resistance, scratch resistance and flexibility of the surface protection film. Preferably, the first carbamate (meth) acrylate oligomer is a nine to ten functional (meth) acrylate oligomer and may have a weight average molecular weight of 1,500 g / mol to 2,500 g / mol and an elongation of 5% to 10%. Within this range, even with a thin hard coating, the surface protection film can achieve improvements in impact resistance, scratch resistance, foldability and wear resistance.

[0077] The second carbamate (meth) acrylate oligomer is a tetra- to hexa-functional (meth) acrylate oligomer and may have a weight average molecular weight of about 4,000 g / mol to about 8,000 g / mol and an elongation of about 15% to about 25%. Within this range, the second carbamate (meth) acrylate oligomer can help improve the impact resistance, scratch resistance and flexibility of the surface protection film. Preferably, the second carbamate (meth) acrylate oligomer is a penta- to hexa-functional (meth) acrylate oligomer and may have a weight average molecular weight of 4,000 g / mol to 6,000 g / mol and an elongation of 15% to 20%. Within this range, even with a thin hard coating, the surface protection film can achieve improvements in impact resistance, scratch resistance, foldability and wear resistance.

[0078] The second urethane (meth) acrylate oligomer may be present in a smaller amount than the first urethane (meth) acrylate oligomer. Therefore, the first and second urethane (meth) acrylate oligomers may help improve the impact resistance, scratch resistance, and flexibility of the surface protection film.

[0079] Specifically, the second urethane (meth) acrylate oligomer may be present in an amount of about 80% to about 200% of the first urethane (meth) acrylate oligomer. Within this range, the surface protection film can achieve improvements in impact resistance, scratch resistance, foldability, and stretching effect even with a thin hard coating.

[0080] In terms of solid content, the first urethane (meth) acrylate oligomer may be present in an amount of about 10 parts by weight to about 50 parts by weight, and the second urethane (meth) acrylate oligomer may be present in an amount of about 40 parts by weight to about 80 parts by weight, relative to 100 parts by weight of the total of the first urethane (meth) acrylate oligomer, the second urethane (meth) acrylate oligomer, the (meth) acrylate monomer, and the aluminum oxide. Within this range, the protective film can exhibit excellent properties in terms of impact resistance, scratch resistance, and foldability.

[0081] For example, the first urethane (meth)acrylate oligomer may be present in an amount of 10, 15, 20, 25, 30, 35, 40, 45, or 50 parts by weight, and the second urethane (meth)acrylate oligomer may be present in an amount of 40, 45, 50, 55, 60, 65, 70, 75, or 80 parts by weight.

[0082] Preferably, the first urethane (meth) acrylate oligomer may be present in an amount of 30 to 50 parts by weight, for example, 30 to 45 parts by weight, and the second urethane (meth) acrylate oligomer may be present in an amount of 40 to 60 parts by weight. Within this range, even with a thin hard coating, the surface protection film can achieve improvements in impact resistance, scratch resistance, and foldability.

[0083] Herein, "in terms of solid content" means the total amount of components in the hard coating composition excluding the solvent.

[0084] Each of the first carbamate (meth) acrylate oligomer and the second carbamate (meth) acrylate oligomer can be prepared by polymerization of a polyfunctional polyol, a polyfunctional isocyanate compound and a hydroxyl-containing (meth) acrylate compound. The polyfunctional polyol may include the above-mentioned polyfunctional polyol, and the polyfunctional isocyanate compound may include the above-mentioned polyfunctional isocyanate compound. The hydroxyl-containing (meth) acrylate compound may include hydroxyethyl (meth) acrylate, pentaerythritol tri (meth) acrylate, dipentaerythritol penta (meth) acrylate, hydroxypropyl (meth) acrylate, hydroxybutyl (meth) acrylate, chlorohydroxypropyl (meth) acrylate and hydroxyhexyl (meth) acrylate, but is not limited thereto.

[0085] The (meth)acrylate monomer is a di- to hexafunctional (meth)acrylate monomer and may be cured together with the first urethane (meth)acrylate oligomer and the second urethane (meth)acrylate oligomer to increase the hardness of the hard coating layer.

[0086] The (meth)acrylate monomer may include a difunctional (meth)acrylate such as 1,4-butanediol di(meth)acrylate, hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, neopentyl glycol adipic acid di(meth)acrylate, dicyclopentyl di(meth)acrylate, caprolactone-modified dicyclopentenyl di(meth)acrylate, ethylene oxide-modified di(meth)acrylate, di(meth)acryloyloxyethyl isocyanurate, allylated cyclohexyl di(meth)acrylate, tricyclodecane dimethanol (meth)acrylate, dimethylol dicyclopentane di(meth)acrylate, ethylene oxide-modified hexahydrophthalic acid di(meth)acrylate, tricyclodecane dimethanol (meth)acrylate, neopentyl glycol-modified trimethylpropane di(meth)acrylate. Ester, adamantane di(meth)acrylate and 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene; trifunctional (meth)acrylates such as trimethylolpropane tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, propionic acid-modified dipentaerythritol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, propylene oxide-modified trimethylolpropane tri(meth)acrylate and tri(meth)acryloyloxyethyl isocyanurate; tetrafunctional (meth)acrylates such as diglycerol tetra(meth)acrylate and pentaerythritol tetra(meth)acrylate; pentafunctional (meth)acrylates such as dipentaerythritol penta(meth)acrylate, etc.; and hexafunctional (meth)acrylates such as dipentaerythritol hexa(meth)acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate, etc., but are not limited thereto. Preferably, the (meth)acrylate monomer is a trifunctional or tetrafunctional (meth)acrylate monomer and impact resistance and scratch resistance may be improved by adjusting the crosslinking density.

[0087] The (meth)acrylate monomer may be present in an amount of about 1 part by weight to about 30 parts by weight, for example, 1, 5, 10, 15, 20, 25 or 30 parts by weight, specifically 5 parts by weight to 20 parts by weight, more specifically 5 parts by weight to 15 parts by weight, relative to 100 parts by weight of the total of the first urethane (meth)acrylate oligomer, the second urethane (meth)acrylate oligomer, the (meth)acrylate monomer and the aluminum oxide. Within this range, the surface protection film can achieve improvements in impact resistance, scratch resistance and foldability even with a thin hard coating.

[0088] In hard coatings, aluminum oxide is used to improve the wear and scratch resistance of the surface protective film. Although silicon dioxide or zirconium oxide particles can be used instead of aluminum oxide, aluminum oxide can achieve mechanical properties in a smaller amount than silicon dioxide or zirconium oxide in the same surface area.

[0089] Alumina can include aluminum oxide particles having an average particle size (D50) of about 200 nm or less, specifically 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm or 200 nm, preferably 200 nm or less, more specifically 5 nm to 100 nm. Within this range, the scratch resistance of the hard coating can be improved without deteriorating the haze.

[0090] Aluminum oxide may be present in an amount of about 0.01 to about 10 parts by weight, for example, 0.01, 0.05, 0.1, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5 or 10 parts by weight, preferably 1 to 4 parts by weight, relative to the sum of 100 parts by weight of the first urethane (meth) acrylate oligomer, the second urethane (meth) acrylate oligomer, the (meth) acrylate monomer and the aluminum oxide. Within this range, the surface protection film can achieve improvements in impact resistance, scratch resistance and foldability even with a thin hard coating.

[0091] The initiator may include a photoinitiator and / or a thermal initiator. Preferably, the initiator includes a photoinitiator to ensure surface uniformity of the hard coating layer by preventing shrinkage of the hard coating composition when it is cured.

[0092] The initiator may include an acetophenone compound, a benzyl ketal compound or a mixture thereof, but is not limited thereto. Preferably, the initiator is an acetophenone compound and is selected from 2,2-dimethoxy-2-phenylacetophenone, 2,2'-diethoxyacetophenone, 2,2'-dibutoxyacetophenone, 2-hydroxy-2-methylpropiophenone, p-tert-butyltrichloroacetophenone, p-tert-butyldichloroacetophenone, 4-chloroacetophenone, 2,2'-dichloro-4-phenoxyacetophenone, 2-methyl-1-(4-(methylthio)phenyl)-2-morpholinopropane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butane-1-one and a mixture thereof.

[0093] The initiator may be present in an amount of about 0.01 to about 10 parts by weight, specifically 1 to 5 parts by weight, relative to 100 parts by weight of the total of the first urethane (meth) acrylate oligomer, the second urethane (meth) acrylate oligomer, the (meth) acrylate monomer, and the aluminum oxide. Within this range, the initiator enables a complete curing reaction and can ensure excellent reactivity without bubble generation and without deterioration of transmittance due to the remaining initiator.

[0094] The hard coating composition may further include fluorine-based additives and / or silicone-based additives.

[0095] Fluorine additives improve the wear resistance, especially the anti-skid property of the hard coating by improving the surface characteristics of the hard coating, and the additives may include typical fluorine additives well known to those skilled in the art. Fluorine additives may include fluorine-modified (meth)acrylates and / or fluorine-modified siloxane compounds.

[0096] The fluorine additive may be present in an amount of about 0.01 to about 5 parts by weight, for example, 0.01, 0.05, 0.1, 1, 2, 3, 4 or 5 parts by weight, specifically 0.1 to 2 parts by weight, relative to 100 parts by weight of the sum of the first urethane (meth) acrylate oligomer, the second urethane (meth) acrylate oligomer, the (meth) acrylate monomer and the aluminum oxide. Within this range, the fluorine additive can improve the surface characteristics of the hard coating without affecting other components.

[0097] The silicone additive improves the surface characteristics of the hard coating and may include typical silicone additives well known to those skilled in the art. For example, the silicone additive may include polyether-modified acrylic polydimethylsiloxane, but is not limited thereto.

[0098] The silicone additive may be present in an amount of about 0.01 to about 5 parts by weight, for example, 0.01, 0.05, 0.1, 1, 2, 3, 4 or 5 parts by weight, specifically 0.1 to 2 parts by weight, 0.1 to 1 part by weight, relative to 100 parts by weight of the sum of the first urethane (meth) acrylate oligomer, the second urethane (meth) acrylate oligomer, the (meth) acrylate monomer and the aluminum oxide. Within this range, the silicone additive can improve the surface characteristics of the hard coating without affecting other components.

[0099] The hard coating composition may also include a solvent to improve the coatability of the hard coating composition. The solvent may include methyl ethyl ketone and methyl isobutyl ketone, but is not limited thereto. The hard coating composition may also include typical additives well known to those skilled in the art to impart other functions to the hard coating. The additives may include antioxidants, stabilizers, surfactants, pigments, antistatic agents, and leveling agents, but are not limited thereto.

[0100] The hard coating layer may have a thickness of about 1.5 μm to less than about 20 μm, specifically 2 μm to 10 μm. Within this range, the hard coating layer may improve the impact resistance and scratch resistance of the surface protection film.

[0101] The hard coating layer may have a refractive index of about 1.40 to about 1.75, specifically 1.45 to 1.65. Within this range, the hard coating layer may have a suitable refractive index relative to the base layer to ensure the excellent optical properties of the surface protection film, while improving screen visibility when the surface protection film is stacked on the upper side of the window film. The refractive index difference between the hard coating layer and the base layer (refractive index of the base layer-refractive index of the hard coating layer) may be 0.3 or less, for example, 0.01 to 0.2. Within this range, the surface protection film may be used in an optical display device.

[0102] The hard coating layer may have a water contact angle of about 100° or more, specifically 100° to 150°, as measured at 25° C. Within this range, the hard coating layer has excellent anti-slip properties to ensure excellent wear resistance.

[0103] A functional layer may be further formed on the upper surface of the hard coating to provide other functions to the surface protection film. For example, the functional layer may provide at least one function selected from the following: anti-reflection, low reflection, anti-glare, anti-fingerprint, anti-pollution, diffusion and refraction functions. The functional layer may be formed on the hard coating by coating a composition for the functional layer thereon, or the functional layer may be stacked on the hard coating by a bonding layer or an adhesive layer. In another embodiment, the functional layer may be realized by a surface of the hard coating.

[0104] Adhesive layer

[0105] An adhesive layer is formed on the lower surface of the base layer to attach the surface protection film to the optical element.

[0106] The adhesive layer may have a thickness of about 10 μm to about 50 μm, specifically 10 μm to 25 μm. Within this range, the adhesive layer may be used for the surface protection film without affecting flexibility.

[0107] The adhesive layer may have a storage modulus of about 10 kPa to about 500 kPa, for example, 10 kPa, 20 kPa, 30 kPa, 40 kPa, 50 kPa, 60 kPa, 70 kPa, 80 kPa, 90 kPa, 100 kPa, 120 kPa, 130 kPa, 140 kPa, 150 kPa, 160 kPa, 170 kPa, 180 kPa, 190 kPa, 200 kPa, 300 kPa, 400 kPa or 500 kPa, specifically 10 kPa to 300 kPa, 10 kPa to 200 kPa or 10 kPa to 150 kPa, as measured at -20° C. Within this range, the adhesive layer may improve folding reliability at low temperatures while maintaining adhesion to the base layer.

[0108] The adhesive layer may have a storage modulus of about 10 kPa to about 500 kPa, for example, 10 kPa, 20 kPa, 30 kPa, 40 kPa, 50 kPa, 60 kPa, 70 kPa, 80 kPa, 90 kPa, 100 kPa, 120 kPa, 130 kPa, 140 kPa, 150 kPa, 160 kPa, 170 kPa, 180 kPa, 190 kPa, 200 kPa, 300 kPa, 400 kPa or 500 kPa, specifically 10 kPa to 150 kPa, as measured at 60° C. Within this range, the adhesive layer may improve folding reliability at high temperatures while maintaining adhesion to the base layer.

[0109] The adhesive layer may have a refractive index of about 1.45 to about 1.65, specifically 1.45 to 1.55. Within this range, the adhesive layer has a suitable refractive index with respect to the base layer to ensure a good appearance of the surface protection film.

[0110] The adhesive layer may have a peel strength of 40 gf / in or more, specifically 50 gf / in to 400 gf / in, as measured relative to a SUS surface at 25° C. using a peel strength tester (TA.XT_Plus Texture Analyzer, StableMicro System Inc.) at a peel angle of 180° and a peel rate of 300 mm / min after coating the adhesive resin on the base layer, i.e., the polyurethane film formed by the solution casting method. Within this range, the adhesive layer can ensure excellent folding reliability and enable easy detachment from the outermost surface of the foldable display panel when attached thereto at room temperature.

[0111] The adhesive layer may include a layer formed by an adhesive composition, the adhesive composition including at least one selected from the following: a (meth) acrylic adhesive resin, a silicone adhesive resin, a urethane adhesive resin, and an epoxy adhesive resin. Preferably, in terms of supply and demand, ease of production, excellent appearance, and folding reliability, the adhesive layer is formed by an adhesive composition including a (meth) acrylic adhesive resin or a silicone adhesive resin.

[0112] The adhesive layer may be formed from the adhesive composition by photocuring, thermal curing, or a combination thereof. Photocuring or thermal curing may be performed by typical methods well known to those skilled in the art.

[0113] In one embodiment, the adhesive layer may include a (meth)acrylic adhesive layer formed of an adhesive composition including a monomer mixture of a hydroxyl-containing (meth)acrylic copolymer, particles or a mixture of particles including organic particles and / or inorganic particles, and an initiator.

[0114] The monomer mixture may include a hydroxyl-containing (meth)acrylate; and a comonomer containing at least one selected from the following: an alkyl-containing (meth)acrylate, an ethylene oxide-containing monomer, a propylene oxide-containing monomer, an amine-containing monomer, an alkoxy-containing monomer, a phosphate-containing monomer, a sulfonic acid-containing monomer, a phenyl-containing monomer, a silane-containing monomer, a carboxylic acid-containing monomer, and an amide-containing (meth)acrylate.

[0115] The hydroxyl-containing (meth)acrylate may include at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 1,4-cyclohexanedimethanol mono(meth)acrylate, 1-chloro-2-hydroxypropyl (meth)acrylate, diethylene glycol mono(meth)acrylate, 1,6-hexanediol mono(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, neopentyl glycol mono(meth)acrylate, trimethylolpropane di(meth)acrylate, trimethylolethane di(meth)acrylate, 2-hydroxy-3-pentyloxypropyl (meth)acrylate, 4-hydroxycyclopentyl (meth)acrylate, 4-hydroxycyclohexyl (meth)acrylate, and cyclohexanedimethanol mono(meth)acrylate.

[0116] The alkyl-containing (meth)acrylate may include unsubstituted C1 to C 20Straight or branched alkyl (meth) acrylate. For example, the alkyl-containing (meth) acrylate may include at least one selected from the group consisting of methyl (meth) acrylate, ethyl (meth) acrylate, propyl (meth) acrylate, n-butyl (meth) acrylate, tert-butyl (meth) acrylate, isobutyl (meth) acrylate, pentyl (meth) acrylate, hexyl (meth) acrylate, heptyl (meth) acrylate, ethylhexyl (meth) acrylate, octyl (meth) acrylate, isooctyl (meth) acrylate, nonyl (meth) acrylate, decyl (meth) acrylate, lauryl (meth) acrylate, and isobornyl (meth) acrylate.

[0117] Each of the ethylene oxide-containing monomer, the propylene oxide-containing monomer, the amine group-containing monomer, the alkoxy group-containing monomer, the phosphoric acid group-containing monomer, the sulfonic acid group-containing monomer, the phenyl group-containing monomer, the silane group-containing monomer, the carboxylic acid group-containing monomer and the amide group-containing (meth)acrylate can be selected from typical types known to those skilled in the art.

[0118] Preferably, the monomer mixture includes about 5wt% to about 40wt%, specifically 10wt% to 30wt% of the hydroxyl-containing (meth) acrylate and about 60wt% to about 95wt%, specifically 70wt% to 90wt% of the comonomer. Within this range, the monomer mixture can improve the adhesive strength of the adhesive layer and the flexibility at low and high temperatures.

[0119] In the adhesive layer, the particles serve to improve the flexibility of the surface protective film at low and / or high temperatures or to help significantly improve the impact resistance of the surface protective film.

[0120] Organic particles can further improve the reliability of the adhesive layer at high temperatures by controlling the modulus of the adhesive layer at high temperatures to prevent peeling, warping and / or bubble generation of the adhesive layer at high temperatures. Organic nanoparticles have a high glass transition temperature to improve the modulus of the adhesive layer at high temperatures.

[0121] The organic particles may be organic nanoparticles having an average particle diameter of about 10 nm to about 400 nm, specifically 10 nm to 300 nm, more specifically 30 nm to 280 nm, more specifically 50 nm to 280 nm. Within this range, the organic particles do not affect the foldability of the adhesive layer and have a light transmittance of 90% or more in the visible spectrum to ensure excellent transparency of the adhesive layer.

[0122] The organic particles may have a core-shell structure or a simple structure, such as bead-type nanoparticles, but are not limited thereto. Preferably, the organic particles with a core-shell structure can improve the folding reliability of the surface protection film at both low and high temperatures. The core and the shell satisfy the following relationship (1). That is, both the core and the shell can be organic particles. For organic particles with a core-shell structure, the adhesive layer can show excellent foldability and a balance between elasticity and flexibility.

[0123] Tg(c) <Tg(s),---(1)

[0124] Wherein Tg(c) is the glass transition temperature of the core (unit: °C), and Tg(s) is the glass transition temperature of the shell (unit: °C).

[0125] The glass transition temperature of the core is about -150°C to 10°C, specifically about -150°C to about -5°C, more specifically about -150°C to about -20°C. Within this range, the adhesive layer can have excellent viscoelasticity at low temperatures and / or room temperature. The core may include at least one selected from poly((meth) alkyl acrylates), polysiloxanes, and polybutadiene having the above-mentioned glass transition temperatures, respectively. The poly((meth) alkyl acrylates) may include at least one selected from the following: poly(methyl acrylate), poly(ethyl acrylate), poly(propyl acrylate), poly(butyl acrylate), poly(isopropyl acrylate), poly(hexyl acrylate), poly(hexyl methacrylate), poly(ethylhexyl acrylate), poly(ethylhexyl methacrylate), and polysiloxanes, but is not limited thereto.

[0126] The shell may have a glass transition temperature of about 15°C to about 150°C, specifically about 35°C to about 150°C, more specifically about 50°C to about 140°C. Within this range, the organic nanoparticles may show excellent dispersibility in the (meth) acrylic copolymer. The shell may include a poly(alkyl methacrylate) having the above-mentioned glass transition temperature. For example, the shell may include at least one selected from the following: poly(methyl methacrylate) (PMMA), poly(ethyl methacrylate), poly(propyl methacrylate), poly(butyl methacrylate), poly(isopropyl methacrylate), poly(isobutyl methacrylate) and poly(cyclohexyl methacrylate), but is not limited thereto.

[0127] In the organic particles, the core may be present in an amount of about 30wt% to about 99wt%, specifically about 40wt% to about 95wt%, more specifically about 50wt% to about 90wt%. Within this range, the adhesive layer may show excellent foldability over a wide temperature range. In the organic particles, the shell may be present in an amount of about 1wt% to about 70wt%, specifically about 5wt% to about 60wt%, more specifically about 10wt% to about 50wt%. Within this range, the adhesive layer may show excellent foldability over a wide temperature range.

[0128] The organic particles may optionally be present in an amount of about 20 parts by weight or less, for example, 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20 parts by weight, specifically 0.1 to 20 parts by weight, 0.5 to 10 parts by weight or 0.5 to 8 parts by weight, relative to 100 parts by weight of a monomer mixture comprising a hydroxyl-containing (meth) acrylate and a comonomer. Within this range, the organic particles can ensure excellent properties in terms of the modulus of the adhesive layer at high temperature, the foldability of the adhesive layer at room temperature and at high temperature, and the viscoelasticity of the adhesive layer at low temperature and / or at room temperature.

[0129] Inorganic particles are particles formed of inorganic materials and can help improve the impact resistance of the surface protection film. The inorganic particles may include, for example, metal oxides such as silicon dioxide, zirconium oxide, etc.; metal titanates such as barium titanate, etc.; sulfides (sulfate, sulfate), selenides and tellurides. Preferably, the inorganic particles include silicon dioxide to improve the impact resistance, while preventing the haze of the bonding layer from increasing by reducing the difference in refractive index between the inorganic particles and the bonding resin forming the bonding layer.

[0130] Inorganic particles can include inorganic particles whose average grain size is less than organic particles. Therefore, effect of the present invention can be easily achieved. Inorganic particles are nanoparticles and can have about 10nm to about 200nm, for example, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm or 200nm, specifically 10nm to 150nm, more specifically the average grain size (D50) of 10nm to 100nm. Within this range, the inorganic particles can improve the impact resistance of the surface protective film without affecting the foldability of the surface protective film, and can have a light transmittance of 90% or more and a haze of less than 1% in the visible spectrum to ensure excellent transparency of the adhesive layer.

[0131] Inorganic particles can be optionally relative to 100 parts by weight of a monomer mixture including a hydroxyl-containing (meth) acrylate and a comonomer, with about 20 parts by weight or less, for example, 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20 parts by weight, specifically 0.1 to 20 parts by weight, 0.5 to 10 parts by weight or 0.5 to 8 parts by weight. Within this range, inorganic particles can significantly improve the impact resistance of the surface protection film without affecting the flexibility of the surface protection film.

[0132] The initiator is substantially the same as that described above for use in the hardcoat composition.

[0133] The initiator may be present in an amount of about 0.001 to about 10 parts by weight, specifically 0.001 to 5 parts by weight, relative to 100 parts by weight of a monomer mixture comprising a hydroxyl-containing (meth) acrylate and a comonomer. Within this range, the initiator enables formation of an adhesive layer while preventing the transparency of the surface protection film from deteriorating.

[0134] The adhesive composition may further include silicone-based (meth)acrylates. The silicone-based (meth)acrylates may improve foldability and improve adhesion of the adhesive layer to the base layer by improving wettability of the adhesive layer to the base layer.

[0135] Silicone (meth) acrylates are siloxane-modified monofunctional or multifunctional (meth) acrylates and can be obtained from typical products well known to those skilled in the art. For example, silicone (meth) acrylates may include modified silicones having (meth) acrylate groups at one end thereof and / or modified silicones having (meth) acrylate groups at both ends thereof.

[0136] The silicone-based (meth)acrylate may be present in an amount of about 5 parts by weight or less, for example, about 0.001 parts by weight to about 5 parts by weight, specifically 0.001 parts by weight to 3 parts by weight, relative to 100 parts by weight of the monomer mixture including the hydroxyl-containing (meth)acrylate and the comonomer. Within this range, the surface protection film can ensure excellent wettability when attached to the outermost surface of the foldable panel.

[0137] The adhesive composition may further include a crosslinking agent and a silane coupling agent. The crosslinking agent may include a difunctional to hexafunctional (meth)acrylate-based photocurable monomer. The detailed information is well known to those skilled in the art.

[0138] In another embodiment, the adhesive layer may include a silicone-based adhesive layer formed of a silicone-based adhesive composition including an alkenyl-containing organopolysiloxane and a cross-linking agent.

[0139] The alkenyl-containing organopolysiloxane may include component (i) and / or component (ii):

[0140] Component (i): having at least one Si-coupled C3 to C 10 Alkenyl organopolysiloxane

[0141] Component (ii): an organopolysiloxane having at least one Si-coupled vinyl group per molecule.

[0142] Component (i) may include an organopolysiloxane represented by Formula 1:

[0143] (R 1 R 2 SiO 2 / 2 ) x (R 3 R 4 SiO 2 / 2 ) y ,

[0144] Where R 1 C3 to C 10 alkenyl;

[0145] R 2 C1 to C 10 alkyl;

[0146] R 3and R 4 Each independently is C1 to C 10 alkyl; and

[0147] 0 < x ≤ 1, 0 ≤ y < 1, and x + y = 1.

[0148] Preferably, x and y satisfy the following relationship: 0.001 ≤ x ≤ 0.4, 0.6 ≤ y ≤ 0.999, and x + y = 1, more preferably 0.005 ≤ x ≤ 0.2, 0.8 ≤ y ≤ 0.995, and x + y = 1.

[0149] Component (ii) can be an organopolysiloxane having at least one Si-coupled vinyl group in its side chain or at both ends thereof.

[0150] In one embodiment, component (ii) can be an organopolysiloxane having at least one Si-coupled vinyl group at both ends thereof. For example, component (ii) can be an organopolysiloxane represented by Formula 2:

[0151] R 5 R 6 R 7 SiO(R 1 R 2 SiO 2 / 2 )x(R 3 R 4 SiO 2 / 2 )ySiR 8 R 9 R 10 ,

[0152] wherein R 1 , R 2 , R 3 and R 4 each independently is C1 to C 10 alkyl;

[0153] R 5 , R 6 and R 7 each independently is vinyl or C1 to C 10 alkyl, and at least one of R 5 , R 6 and R 7 is vinyl;

[0154] R 8 , R 9 and R 10 each independently is vinyl or C1 to C 10 alkyl; and at least one of R 8 , R 9 and R 10 is vinyl; and

[0155] 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, and x + y = 1.

[0156] In another embodiment, component (ii) can be an organopolysiloxane having at least one Si-coupled vinyl in its side chain. For example, component (ii) can be an organopolysiloxane represented by Formula 3:

[0157] (R 1 R 2 SiO 2 / 2 )x(R 3 R 4 SiO 2 / 2 )y(R 5 R 6 SiO 2 / 2 )z,

[0158] wherein R 1 , R 2 , R 3 , R 4 , R 5 and R 6 are each independently a C1 to C 10 alkyl, vinyl or a C6 to C 10 aryl, and at least one of R 1 and R 2 is vinyl; and

[0159] 0 < x ≤ 1, 0 ≤ y < 1, 0 ≤ z < 1, and x + y + z = 1.

[0160] In another embodiment, component (ii) can be an organopolysiloxane having at least one Si-coupled vinyl in its side chain. For example, component (ii) can be an organopolysiloxane represented by Formula 4:

[0161] (R 1 R 2 SiO 2 / 2 )x(R 3 R 4 SiO 2 / 2 )y,

[0162] wherein R 1 , R 2 , R 3 and R 4 are each independently a C1 to C 10 alkyl, vinyl or a C6 to C 10 aryl, and at least one of R 1 and R 2 is vinyl; and

[0163] 0 < x ≤ 1, 0 ≤ y < 1, and x + y = 1.

[0164] The crosslinking agent may include a hydrogen-containing organopolysiloxane having at least two Si-H bonds in its molecule. In one embodiment, the crosslinking agent may be represented by Formula 5:

[0165] R 4 R 5 R 6 SiO(R 1 R 2 SiO 2 / 2 )x(HR 3 SiO 2 / 2 )ySiR 7 R 8 R 9 ,

[0166] wherein R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 and R 9 are each independently a C1 to C 10 alkyl group; and

[0167] 0 ≤ x < 1, 0 < y ≤ 1, and x + y = 1.

[0168] The adhesive composition may further include an organopolysiloxane resin. The organopolysiloxane resin includes R 1 R 2 R 3 SiO 1 / 2 units (“M units”) and SiO 4 / 2 units (“Q units”). In this formula, R 1 , R 2 and R 3 are each independently a C1 to C6 alkyl group or a C2 to C 10 alkenyl group, for example, methyl, ethyl, isopropyl or propyl, such as n-propyl, etc., vinyl or alkenyl, such as allyl, etc.

[0169] The adhesive composition may further include a hydrosilylation catalyst. The hydrosilylation catalyst promotes the reaction between the organopolysiloxane and the crosslinking agent. The hydrosilylation catalyst may include a platinum-based catalyst, a ruthenium-based catalyst or an osmium-based catalyst. Specifically, typical platinum catalysts well-known to those skilled in the art. For example, the hydrosilylation catalyst may include chloroplatinic acid, an alcoholic solution of chloroplatinic acid, a complex of chloroplatinic acid and an olefin, a complex of chloroplatinic acid and a vinylsiloxane, etc.

[0170] The optical member according to the present invention includes the surface protection film according to the present invention.

[0171] According to one embodiment, an optical member includes an optical element and the surface protection film of the present invention stacked on at least one surface of the optical element.

[0172] The optical element may include a plurality of optical components in a display device. Preferably, since the surface protection film according to the present invention includes a hard coating, the optical element includes a window film. The optical member may include a surface protection film and a window film according to the present invention stacked one after another in sequence when viewed from the observer side.

[0173] The window film may include a base layer and a hard coating layer formed of a silicone resin for foldability, but is not limited thereto. In one embodiment, the window film includes a base layer and a hard coating layer formed on an upper surface of the base layer, and may further include a functional layer, for example, an anti-fingerprint layer, on an upper surface of the hard coating layer.

[0174] The display device according to the present invention includes the surface protection film according to the present invention. The display device may include a flexible display device or a non-flexible display device.

[0175] According to one embodiment, a display device may include an optical element and the surface protection film of the present invention stacked on at least one surface of the optical element.

[0176] The optical element may include a plurality of optical components in a display device. Preferably, since the surface protection film according to the present invention includes a hard coating, the optical element includes a window film. The optical member may include a surface protection film and a window film according to the present invention stacked one after another in sequence when viewed from the observer side.

[0177] The window film may include a base layer and a hard coating layer formed of a silicone resin for foldability, but is not limited thereto.

[0178] The display device may further include a display drive unit for driving the display device. The display drive unit may include an optical element, which includes an organic light emitting diode (OLED), an LED, a QLED (quantum dot light emitting diode), an LCD element, and a quantum dot element. The display drive unit may further include a substrate for maintaining the optical element.

[0179] The display device may further include a polarizing plate. The polarizing plate may enable the display device or improve the contrast of the display device by polarizing the internal light or by preventing external light reflection. The polarizing plate may consist of a polarizer alone. Alternatively, the polarizing plate may include a polarizer and a protective film on one or both surfaces of the polarizer. Alternatively, the polarizing plate may include a polarizer and a protective coating on one or both surfaces of the polarizer. Each of the polarizer, protective film, and protective coating may be derived from a typical product well known to those skilled in the art.

[0180] The display device may also include a touch screen panel. When contacted by a conductor such as a human body or an input pen, the touch screen panel may generate an electrical signal by detecting a change in capacitance, thereby driving the display driving unit in response to the electrical signal.

[0181] Then, the present invention will be described in more detail with reference to Examples. However, it should be noted that these Examples are provided for illustration only and should not be construed as limiting the present invention in any way.

[0182] The components of the hard coating composition used in Examples and Comparative Examples are shown below.

[0183] (A) First urethane (meth)acrylate oligomer: UA11064 (Entis Co., Ltd., decafunctional (meth)acrylate, weight average molecular weight: 2,000, elongation: 6%, solid content: 100%)

[0184] (B) Second urethane (meth)acrylate oligomer: CHTF-9696AN (Chemton Co., Ltd., hexafunctional (meth)acrylate, weight average molecular weight: 4,500, elongation: 16%, solid content: 83%)

[0185] (C) (Meth)acrylate monomer: SR499 (Sartomer Co., Ltd., trifunctional (meth)acrylate, solid content: 100%)

[0186] (D) Alumina: LAA530U (Ranco Co., Ltd., average particle size (D50): 15 nm, solid content: 30%)

[0187] (E) Fluorine additive: RS-78 (DIC Co., Ltd., solid content: 10%)

[0188] (F) Initiator: Irgacure 184 (BASF, solid content: 25%)

[0189] (G) Solvent: Methyl ethyl ketone (Samchun Chemicals Co., Ltd.)

[0190] *For the first urethane (meth)acrylate oligomer and the second urethane (meth)acrylate oligomer, the elongation was evaluated by an Instron test method according to JIS K7311.

[0191] Example 1

[0192] (1) Preparation of hard coating composition

[0193] In terms of solid content, 30 parts by weight of a first urethane (meth)acrylate oligomer, 60 parts by weight of a second urethane (meth)acrylate oligomer, 7 parts by weight of a (meth)acrylate monomer, 3 parts by weight of aluminum oxide particles, 0.4 parts by weight of a fluorine-based additive, and 2.5 parts by weight of an initiator were mixed with 50 parts by weight of methyl ethyl ketone as a solvent, thereby preparing a hard coating composition.

[0194] (2) Preparation of Adhesive Composition ((Meth)Acrylic Adhesive Layer)

[0195] The organic nanoparticles were prepared by emulsion polymerization. The organic nanoparticles included 35 wt % of a shell and 65 wt % of a core, wherein the core was poly(butyl acrylate) and the shell was poly(methyl methacrylate), and had an average particle size of 200 nm and a refractive index of 1.48.

[0196] As inorganic nanoparticles, silica particles (Optisol-ASAM0151, Racno Co., Ltd., silica average particle size (D50): 90 nm) were used.

[0197] 100 parts by weight of a monomer mixture containing 20 parts by weight of 4-hydroxybutyl acrylate, 80 parts by weight of 2-ethylhexyl acrylate and 0.03 parts by weight of an initiator (Irgacure 651, 2,2-dimethoxy-2-phenylacetophenone, BASF) were mixed in a reactor. After the dissolved oxygen in the reactor was replaced with nitrogen, the mixture was partially polymerized by UV irradiation using a low-pressure mercury lamp, thereby preparing a viscous liquid having a viscosity of 5,000 cP at 25°C.

[0198] In terms of solid content, 0.5 parts by weight of an initiator (Irgacure 184, 1-hydroxycyclohexylphenone, BASF), 5 parts by weight of organic nanoparticles, and 5 parts by weight of inorganic nanoparticles were added to a reactor and mixed with a viscous liquid to prepare an adhesive composition.

[0199] The adhesive composition was deposited on one surface of a release film (polyethylene terephthalate film) and irradiated at 2,000 mJ / cm 2 The adhesive layer was irradiated with UV light at a dose of 100 μm, thereby preparing an adhesive sheet of a 25 μm thick adhesive layer and a PET film. The adhesive layer had a storage modulus of 100 kPa at -20°C and a storage modulus of 20 kPa at 60°C. The storage modulus was measured using a dynamic viscoelasticity instrument (ARES G2, TA Instrument) by the method described below.

[0200] (3) Preparation of surface protective film

[0201] The hard coating composition was applied to the upper surface of a cast polyurethane film (prepared by a solution casting method) (thickness: 100 μm, haze: 1%) used as a base layer and dried at 80° C. for 2 minutes, and then heated at 300 mJ / cm 2 The substrate was irradiated with a dose of 2 μm under a light source (metal halide lamp) while purging with nitrogen to form a hard coating layer (thickness: 2 μm) on the upper surface of the base layer.

[0202] The prepared adhesive composition was applied to the lower surface of the cast polyurethane film and irradiated at 2,000 mJ / cm 2 The substrate was irradiated with UV light at a dose of 1000 μm to form an adhesive layer (thickness: 25 μm) on the lower surface of the base layer, thereby preparing a surface protective film.

[0203] Examples 2 to 4

[0204] A surface protection film was produced in the same manner as in Example 1, except that the cast polyurethane film and the adhesive layer were changed as listed in Table 1.

[0205] Example 5

[0206] (1) Preparation of adhesive composition (silicone adhesive layer)

[0207] Silicone resin (Shin-Etsu Chemical Co., Ltd., X-40-3229, K3700K) was dissolved in toluene to have a solid content of 30% and mixed for 30 minutes. Then, 0.5 parts by weight of a Pt catalyst was added to the mixture and mixed for 30 minutes, thereby preparing a silicone-based adhesive composition.

[0208] The adhesive layer formed of the silicone adhesive composition has a storage modulus of 200 kPa at -20°C and a storage modulus of 20 kPa at 60°C. The storage modulus is measured by a dynamic viscoelasticity meter (ARES G2, TA Instrument) by the method described below. The adhesive layer having a thickness of 10 μm has an adhesive strength of 40 gf / 25 mm or more relative to the anti-fingerprint layer.

[0209] (2) Preparation of surface protective film

[0210] The hard coating composition prepared in Example 1 was coated on the upper surface of the cast polyurethane film used as the base layer and dried at 80° C. for 2 minutes, and then heated at 300 mJ / cm 2 The substrate was irradiated with a dose of 2 μm under a light source (metal halide lamp) while purging with nitrogen to form a hard coating layer (thickness: 2 μm) on the upper surface of the base layer.

[0211] The prepared adhesive composition was applied to the lower surface of the cast polyurethane film, dried at 130° C. for 3 min, and maintained at 40° C. for 3 days to form an adhesive layer (thickness: 15 μm) on the lower surface of the base layer, thereby preparing a surface protection film.

[0212] Comparative Example 1

[0213] A surface protection film was produced in the same manner as in Example 1, except that a thermoplastic polyurethane (TPU) film (Sheedom Co., Ltd., haze: 1%) was used instead of the cast polyurethane film.

[0214] Comparative Example 2

[0215] A surface protection film was produced in the same manner as in Example 1, except that a thermoplastic polyurethane (TPU) film (Sheedom Co., Ltd.) was used instead of the cast polyurethane film and a silicone adhesive (Shin-Etsu Chemical Co., Ltd.) was used to form the adhesive layer.

[0216] Comparative Example 3

[0217] A surface protection film was produced in the same manner as in Example 1, except that the cast polyurethane film of Table 1 was used.

[0218] The surface protection films of Examples and Comparative Examples were evaluated for the following properties, and the results are shown in Table 1.

[0219] (1) Young's modulus of base layer (unit: MPa): The Young's modulus was evaluated at 25° C. with respect to the base layer of each surface protection film prepared in the examples and comparative examples. The Young's modulus was evaluated using a V-type test specimen according to ASTM D638. Specifically, the Young's modulus was evaluated at 100 mm / min by a tensile test experiment using a UTM system (Intron Technology Co., Ltd.).

[0220] (2) Storage modulus of base layer (unit: MPa): The storage modulus was evaluated at -20°C and 85°C relative to the base layer of each surface protection film prepared in the examples and comparative examples. The storage modulus was measured using a dynamic mechanical analyzer (DMA) system. Specifically, the storage modulus at -20°C and 85°C was measured in a tensile test mode at a frequency of 1 Hz while the temperature was raised from -70°C to 120°C at a heating rate of 2°C / min.

[0221] (3) Elongation at break of base layer (unit: %): The elongation at break was evaluated relative to the base layer of each surface protection film prepared in the examples and comparative examples. The elongation at break was evaluated using a V-type test specimen at 25° C. according to ASTM D638. Specifically, the elongation at break was evaluated at 100 mm / min by a tensile test experiment using a UTM system (Intron Technology Co., Ltd.).

[0222] (4) Storage modulus of hard coating and base layer (unit: MPa): The storage modulus at -20°C and 85°C was evaluated for the laminate of the hard coating and base layer of each surface protection film prepared in the examples and comparative examples. The storage modulus was measured using a dynamic mechanical analyzer (DMA) system. Specifically, the storage modulus at -20°C and 85°C was measured at a frequency of 1 Hz in a tensile test mode while the temperature was increased from -70°C to 120°C at a heating rate of 2°C / min.

[0223] (5) Pen drop impact resistance: A specimen was prepared by sequentially stacking a polyethylene terephthalate (PET) film (thickness: 38 μm), an adhesive film (thickness: 25 μm, storage modulus at 25° C. of 0.03 MPa), and a PET film (thickness: 125 μm) on the lower surface of the adhesive layer of each surface protective film prepared in Examples and Comparative Examples. A ballpoint pen (BIC Co., Ltd., Crystal Materials, A pen (of 100 cm) is dropped from a predetermined height above the hard coating of the sample to evaluate the initial height of the dent formed on the bottommost PET film (thickness: 125 μm). The maximum height of the dent formed thereon is evaluated for simulation or comparison of the height of the bright spot where the pixel will be destroyed and the height of the broken window glass in the real foldable panel, and can be confirmed by a magnifying glass or an optical microscope. A higher initial height indicates better resistance to pen drop impact. A height of 18 cm or more indicates that the surface protective film has excellent impact resistance to be suitable for panels in practice.

[0224] (6) Bending reliability: A sample (length × width: 10 cm × 5 cm) was prepared by stacking a polyethylene terephthalate film (thickness: 75 μm) on the lower surface of the adhesive layer of each surface protective film prepared in the examples and comparative examples. The sample was evaluated at -20°C and 60°C for crack generation at the bent portion of the sample by repeating 100,000 cycles of folding and unfolding the sample on the polyethylene terephthalate film side so that the bent portion of the sample had a radius of curvature of 1.5 mm, wherein each cycle refers to an operation of folding the sample in half in its longitudinal direction and then unfolding the sample. An evaluation of ○ was given for no crack generation even after 100,000 cycles of folding and unfolding, △ was given for one crack generation, and X was given for two or more crack generation.

[0225] (7) Appearance: The appearance of each of the surface protective films of the embodiments and comparative examples on the hard coating side was observed with the naked eye by irradiating the surface protective film with light from a xenon lamp, and an evaluation of ○ was given when there was no streak pattern, gel and / or opacity on the entire surface protective film, and an evaluation of X was given when there was even a slight streak pattern, gel and / or opacity on it.

[0226] (8) Scratch resistance: A sample was prepared by stacking a polyethylene terephthalate film (thickness: 75 μm) on the lower surface of the adhesive layer of the protective film of the window film used in the embodiments and comparative examples. By fixing the sample to a surface property tester (Heidon Co., Ltd.) and #0000 steel wool fixed thereon, a weight of 500 g was reciprocated 10 times on the surface of the hard coating on a scale of 50 mm to evaluate the number of scratches thereon. The fewer the number of scratches, the higher the scratch resistance. In the evaluation of scratch resistance, two or less scratches indicate that the surface protective film has high scratch resistance and can be applied to display devices. (Less than 2: ○, 2 to 10: Δ, greater than 10: X)

[0227] (9) Abrasion resistance: The hard coating surface of each surface protection film of Examples and Comparative Examples was observed with naked eyes after wiping the hard coating surface several times with an eraser-fixed tip under a load of 500 g. The number of initial scratches on the hard coating surface was evaluated.

[0228] Table 1

[0229]

[0230] As shown in Table 1, the surface protection film according to the present invention has excellent impact resistance, excellent folding reliability at both low and high temperatures and has an excellent appearance. In addition, the surface protection film shows excellent scratch resistance and excellent wear resistance. Therefore, the present invention provides a surface protection film having excellent impact resistance and excellent folding reliability at low and high temperatures. The present invention provides a surface protection film that achieves improvements in wear resistance, scratch resistance and anti-slip properties. The present invention provides a surface protection film with excellent appearance.

[0231] In contrast, as shown in Table 1, the surface protection films of the comparative examples could not achieve the effects of the present invention.

[0232] Although some embodiments have been described herein, it should be understood that numerous modifications, changes, variations, and equivalent embodiments may be made by those skilled in the art without departing from the spirit and scope of the invention.

Claims

1. A surface protection film comprising: The hard coating, base layer and adhesive layer are stacked in sequence. wherein the base layer comprises a polyurethane film formed by a solution casting method and has a Young's modulus of 80 MPa to 500 MPa at 25° C., wherein the laminate of the hard coating layer and the base layer has a storage modulus of 900 MPa to 1500 MPa at -20°C and a storage modulus of 15 MPa to 100 MPa at 85°C, and Wherein, the base layer has a haze of 1% or less.

2. The surface protection film according to claim 1, wherein The base layer has a thickness of 75 μm to 200 μm.

3. The surface protection film according to claim 1 or 2, wherein: The base layer has an elongation at break measured at 25° C. of 200% or more.

4. The surface protection film according to claim 1 or 2, wherein The base layer has a storage modulus of 900 MPa to 1500 MPa at -20°C and a storage modulus of 15 MPa to 100 MPa at 85°C.

5. The surface protection film according to claim 1 or 2, wherein: The adhesive layer has a storage modulus of 10 kPa to 500 kPa at -20°C and a storage modulus of 10 kPa to 500 kPa at 60°C.

6. The surface protection film according to claim 1 or 2, wherein: The adhesive layer includes a (meth)acrylic adhesive layer, which is formed by an adhesive composition, wherein the adhesive composition includes: a monomer mixture of a hydroxyl-containing (meth)acrylic copolymer, particles or a particle mixture including at least one selected from organic particles and inorganic particles, and an initiator; or a silicone adhesive layer, which is formed by an adhesive composition including an alkenyl-containing organopolysiloxane.

7. The surface protection film according to claim 6, wherein The organic particles include core-shell type organic nanoparticles.

8. The surface protection film according to claim 7, wherein The core-shell organic nanoparticles satisfy the relationship (1): Tg(c) <Tg(s),---(1) Wherein, Tg(c) is the glass transition temperature of the core in °C, and Tg(s) is the glass transition temperature of the shell in °C.

9. The surface protection film according to claim 6, wherein The inorganic particles include at least one selected from the group consisting of metal oxides, metal titanates, sulfides, selenides, and tellurides.

10. The surface protection film according to claim 6, wherein The monomer mixture includes 5 wt % to 40 wt % of a hydroxyl-containing (meth)acrylate and 60 wt % to 95 wt % of a comonomer.

11. The surface protection film according to claim 6, wherein The alkenyl-containing organopolysiloxane comprises at least one selected from component (i) and component (ii): Component (i): having at least one Si-coupled C3 to C 10 alkenyl organopolysiloxane; and Component (ii): an organopolysiloxane having at least one Si-coupled vinyl group per molecule.

12. The surface protection film according to claim 1 or 2, wherein: The hard coating layer is formed by a carbamate (meth)acrylate hard coating composition, which includes: a first carbamate (meth)acrylate oligomer, a second carbamate (meth)acrylate oligomer, a (meth)acrylate monomer, aluminum oxide, an initiator, and at least one selected from a fluorine additive and a silicone additive.

13. The surface protection film according to claim 1 or 2, wherein: The hard coating layer has a water contact angle of 100° or more at 25°C. 14 . An optical member comprising the surface protection film according to claim 1 .

15. The optical component according to claim 14, comprising: Window film; and the surface protection film formed on one surface of the window film.

16. A display device comprising the surface protection film according to claim 1 or 2.

Citation Information

Patent Citations

  • Efficient double-sided tape manufacturing method

    KR1020210004292A

  • TENSIONING device of pull chain of stepped apron of escalator

    UA11064U

  • Optical display device protecting film, optical member comprising same, and optical display device comprising same

    CN109564300A

  • Silicone-based adhesive protection film and optical member comprising same

    WO2020218879A1